Formation of Intellectual Property Forensics in the System of the Russian Ministry of Justice - A. S. Savenko (Теория и практика судебной экспертизы)
The article analyses legal regulations of a forensic investigation into intellectual property o jects regarding the appointment of examinations of trademarks and service marks. The matter of necessity of specialized knowledge to conduct such investigations is addressed as well as current expert and judicial practice in this field. The author notes that forensic analysis of trade and service marks should be carried out as a part of a comprehensive examination in complex cases. The investigation should also include a sociological study.It is shown that the training of state forensic experts in the Russian Ministry of Justice system for intellectual property forensics, among other things to assess its value, will provide fully competent, unbiased, and independent experts and specialists in the field. The author proposes acknowledging and adding to the List of types of forensic examinations conducted in the Federal budget forensic institutions of the Russian Ministry of Justice the new type of forensic examinations – “Intellectual Property Forensics”.